Enhancing self-care in post-MI patients: a family-supported educational intervention based on the theory of planned behavior - Arman, Ali; Attar, Armin; Izadpanah, Peyman; Bahja, Hasan; Jeihooni, Ali Khani (BMC cardiovascular disorders, 2025)
Myocardial Infarction (MI) ranks among the major causes of death and disability globally. The modifiable risk factors are very important not only for its prevention, but also for its long-term management. Adherence to self-care plays a very important part in improving outcomes following MI. However, after MI, patient adherence declines over time. The Theory of Planned Behavior (TPB) is a socio-psychological theory that can be a model to develop focused interventions which will improve self-care practices. This quasi-experimental study was conducted on 140 post-MI patients in Fasa City, Iran (2023-2024). They were randomly allocated to the intervention (70) or control (70) group. Participants in the intervention group received a 10-session education program based on the TPB content related to self-care components. The control group only received standard care. Validated scales assessed self-care behavior, TPB constructs (attitude, subjective norms, perceived behavioral control), lifestyle modification and behavioral intention at baseline and 4-month follow-up. There was no significant difference between both groups in terms of demographic and baseline variables and TPB domains (p > 0.05). However, at four months following the intervention, the intervention group showed a significant improvement in all evaluated variables compared to the control group (p < 0.001). The TPB-based educational intervention can meaningfully improve the self-care behavior of MI patients. Future work should assess the sustainability over time of these changes, and the feasibility of using digital health technology to support enhanced patient compliance.